Effect of Leuconostoc mesenteroides KCCM35046 fermented aged garlic extract on egg production, egg quality, odour gas emissions, targeted E. coli colony, haematological characteristics and fatty acids composition of egg yolk in laying hens. Issue 1 (1st January 2016) - Hossain, M.M.; Begum, M.; Kim, I.H.
ABSTRACT: The design of this study was to investigate the impacts of dietary supplementation with aged garlic extract (AGE) by Leuconostoc mesenteroides KCCM35046 on egg production, egg quality, odour gas emissions from excreta, excreta microbiota, haematological characteristics and fatty acids composition of egg yolk in laying hens. A total of 384, 54-week (ISA-brown) laying hens were randomly assigned to one of four treatments with eight replications per treatment and 12 adjacent cages as a replication. The experimental treatments were: (1) CON; basal diet, (2) AGE.05; CON + .05% aged garlic extract, (3) AGE.1; CON + .1% aged garlic extract, (4) AGE.2; CON + .2% aged garlic extract. No significant differences were observed in feed intake (FI) and egg production among treatments ( P  > .05). Laying hens fed with the AGE linearly improved yolk height at Week 3 ( P  = .02). The inclusion of .1% AGE had increased Haughunit (HU) at Week 4 (quadratic, P  = .01). At the end of the experiment, AGE diet linearly increased yolk height and egg shell thickness ( P  = .01 and .03, respectively). No significant differences were observed in excreta gas emission ( P  > .05). The supplementation of AGE linearly reduced excreta E. coli concentrations ( P  = .02). Inclusion of AGE led to a greater lymphocyte and IgG concentrations (linear, P  = .04 and P  = .03, respectively), whereas blood total cholesterol (TC) was reduced by the AGE supplementation (linear, P  < .01). PUFA: SFA was increased in AGE treatment at the end of the experiment ( P  < .05). In conclusion, the administration of AGE at a level of .1 and/or .2% can improve egg quality, blood lymphocyte, IgG concentrations and reduced excreta E. coli and blood TC in the laying hens.